2018
DOI: 10.1016/j.cell.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Mobilization Reveals a Highly Engraftable Hematopoietic Stem Cell

Abstract: Hematopoietic stem cell transplantation is a potential curative therapy for malignant and nonmalignant diseases. Improving the efficiency of stem cell collection and the quality of the cells acquired can broaden the donor pool and improve patient outcomes. We developed a rapid stem cell mobilization regimen utilizing a unique CXCR2 agonist, GROβ, and the CXCR4 antagonist AMD3100. A single injection of both agents resulted in stem cell mobilization peaking within 15 min that was equivalent in magnitude to a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 44 publications
3
74
0
Order By: Relevance
“…Current efforts toward increasing the yield of transduced cells comprise more effective mobilization and collection regimes, using antagonists of the CXCL12/CXCR4 axis, such as Plerixafor (Broxmeyer et al, 2005), and of the VLA-4/VCAM-1 axis (Ghobadi et al, 2018), which mediate HSPC homing and retention in the marrow niche, and/or granulocyte colony-stimulating factor (G-CSF) and CXCR2 agonists, such as GROb, acting on neutrophils and resulting in MMP-9 secretion, matrix digestion and HSPC release (Hoggatt et al, 2018), and ex vivo expansion of the collected HSPC (see below). The HSPC source, with mobilized peripheral blood now preferred over bone marrow, and the mobilization protocol affect the total amount and proportion of long-term repopulating versus committed progenitor cells in the harvest.…”
Section: Outstanding Challenges and Further Goals Aheadmentioning
confidence: 99%
“…Current efforts toward increasing the yield of transduced cells comprise more effective mobilization and collection regimes, using antagonists of the CXCL12/CXCR4 axis, such as Plerixafor (Broxmeyer et al, 2005), and of the VLA-4/VCAM-1 axis (Ghobadi et al, 2018), which mediate HSPC homing and retention in the marrow niche, and/or granulocyte colony-stimulating factor (G-CSF) and CXCR2 agonists, such as GROb, acting on neutrophils and resulting in MMP-9 secretion, matrix digestion and HSPC release (Hoggatt et al, 2018), and ex vivo expansion of the collected HSPC (see below). The HSPC source, with mobilized peripheral blood now preferred over bone marrow, and the mobilization protocol affect the total amount and proportion of long-term repopulating versus committed progenitor cells in the harvest.…”
Section: Outstanding Challenges and Further Goals Aheadmentioning
confidence: 99%
“…With the goal of developing a safe, rapid single day mobilization regimen, combination mobilization with the CXCR4 antagonist AMD3100/plerixafor and the CXCR2 ligand GROβ, previously shown to mobilize HSPC in mice and rhesus monkeys [18;69;70] and recently also in man [70] was explored. While the CXCR4 signaling axis has been a focus of mechanism of HSPC mobilization, particularly associated with the action of G-CSF the chemokine ligands of the CXCR2 receptor, notably GROβ and IL8, induce rapid HSPC mobilization.…”
Section: New Experimental Pathwaysmentioning
confidence: 99%
“…Single combined injection of GROβ plus AMD3100 mobilized more HSPC in 15 minutes than the number of HSPC mobilized by G-CSF in a 4 day regimen in mice [70]. Extensive biochemical, molecular and genetic evidence all confirmed crosstalk between these neutrophil receptors.…”
Section: New Experimental Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from G-CSF, many other agents, such as stromal cell-derived factor 1a (Hattori et al, 2001;Devine et al, 2008), stem cell factor (Andrews et al, 1992), interleukin 6 (IL-6) (Pojda & Tsuboi, 1990), IL-8 (Laterveer et al, 1995), Grob (Pelus & Fukuda, 2006;Fukuda et al, 2007), or granulocyte-macrophage colony-stimulating factor (GM-CSF) (Gianni et al, 1989) can act as mobilizing factors (reviewed in (Lapid et al, 2008)). Recently, Hoggatt et al (2018) reported rapid mobilization of highly engrafting stem cells with a single injection of Grob and AMD3100 combination.…”
Section: Introductionmentioning
confidence: 99%